2021
DOI: 10.1111/vde.12940
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and specificity of a shortened elimination diet protocol for the diagnosis of food‐induced atopic dermatitis (FIAD)

Abstract: Background -The gold standard to diagnose food allergy in dogs is an eight week elimination diet trial (EDT) followed by a re-challenge. A recent study demonstrated that a shorter EDT is possible if prednisolone is administered initially.Hypothesis/Objectives -The goal was to evaluate the sensitivity and specificity of the EDT based on the number of relapses after prednisolone discontinuation. In addition, the aim was to determine whether the initial treatment length or the replacement of prednisolone with ocl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…These dogs were diagnosed with allergic dermatitis by the primary author, either before developing AS or subsequently during the study period. The diagnoses were based on compatible clinical cutaneous signs, exclusion of other pruritic skin disease and performance of a dietary trial with provocation according to published criteria 28–30 . Thirty‐one (16.3%, 95% exact CI 11.4%–22.4%) had a diagnosis of cAD, whilst 19 (10.0%, 95% exact CI 6.1%–15.2%) had CAFR, and 68 (35.8%, 95% exact CI 29.0%–43.0%) had been diagnosed with a combination of both (Tables 2 and 6).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These dogs were diagnosed with allergic dermatitis by the primary author, either before developing AS or subsequently during the study period. The diagnoses were based on compatible clinical cutaneous signs, exclusion of other pruritic skin disease and performance of a dietary trial with provocation according to published criteria 28–30 . Thirty‐one (16.3%, 95% exact CI 11.4%–22.4%) had a diagnosis of cAD, whilst 19 (10.0%, 95% exact CI 6.1%–15.2%) had CAFR, and 68 (35.8%, 95% exact CI 29.0%–43.0%) had been diagnosed with a combination of both (Tables 2 and 6).…”
Section: Resultsmentioning
confidence: 99%
“…Younger dogs also were more commonly diagnosed with concurrent CAFR or cAD + CAFR. The higher number of visits recorded in the younger dogs until clinical resolution of AS were possibly a consequence of concurrent unmanaged allergic inflammation, which needed to be investigated following application of diagnostic criteria [28][29][30] whilst treating AS. We speculate that the undiagnosed cAD and/or CAFR, might contribute to and delay the resolution of AS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several more recent studies have shown that CAFR can be successfully diagnosed in six weeks or less with appropriate antipruritic control and subsequent withdrawal of therapy. 14,21 In our study the ED allowed four of 18 CAFR dogs (22.22%) to complete their EDT at six weeks because their level of pruritus was considered acceptable at PVAS ≤ 3, they did not show signs of infection and antipruritic medications were discontinued before challenge. The benchmark PVAS ≤ 3 was extrapolated from the inclusion criteria from a previous study.…”
Section: Discussionmentioning
confidence: 99%